Pekan PKD, CITF oversee UMP preparation as Vaccine Administering Centre - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 12 July 2021 - Universiti Malaysia Pahang (UMP) received a delegation from the Pekan District Health Office (PKD) and COVID-19 Immunisation Task Force (CITF) to discuss the initial preparations for the opening of the Vaccine Administering Centre (PPV) at UMP Pekan.